Analisis Beban Kerja Tenaga Rekam Medis Rumah Sakit Bedah Surabaya Menggunakan Metode FTE - Dwi Trisana Wardanis (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Workload analysis is a human resource planning activity to determine staffs’ needs, so organization goals can be achieved. Human resource planning at Rumah Sakit Bedah Surabaya is done periodically by using Workload Indicator Staff Need (WISN). Based on the calculation of WISN method, there is a discrepancy between the number of existing and required staffs in the Medical Record Unit of Rumah Sakit Bedah Surabaya. There is an excess of medical record staffs that will impact on employee’s productivity. Therefore, it is so important to measure the workload based on real condition. There are several methods that can be used to analyze the workload. One of them is Full Time Equivalent (FTE). Data of the workload were obtained with interview and daily log which will be analyzed and converted into FTE index. Based on the results, it is found that the workload of supervisor and medical recorder in the morning shift is normal, but those in afternoon and night shift and helpers are underload. The medical record staffs in Rumah Sakit Bedah Surabaya has been sufficient to handle the patient's medical record needs Keywords: full time equivalent, medical record, workload analysis